KEWENANGAN KEJAKSAAN MENGAJUKAN PERMOHONAN PEMBUBARAN PERSEROAN TERBATAS - Gede Agung, I Bagus Putra (Kertha Semaya : Journal Ilmu Hukum, 2020)
The purpose of this study is to analyze first the authority of the Prosecutor's Office submitting a request to dissolve a Limited Liability Company; and second, the criteria for violating the public interest as a basis or reason for submitting a petition for the liquidation of a limited company by the prosecutor. The research method used is normative juridical legal research using a statutory and conceptual. The results showed first, t he authority of the Prosecutor's Office submitting a petition for the dissolution of a Limited Liability Company is regulated in the opening of paragraph IV of the 1945 Constitution of the Republic of Indonesia, which contains the aim of the State to create public welfare, public order. If there is a Limited Liability Company that can hamper the State's objective, then the State gives the authority to the Prosecutor's Office. The Attorney General's Office as a Lawyer for requesting that Disbursement; and second, the criteria for Public Interest Violations by Limited Liability Companies according to the Prosecutor's Office include interfering with the interests of the state, the wider community, and the interests of the nation. Then the Prosecutor's Office must be thorough and know what the criteria for Public Interest Violations are based on various laws that govern what is the public interest. Tujuan penelitian ini untuk menganalisis pertama, kewenangan Kejaksaan mengajukan permohonan pembubaran Perseroan Terbatas ; dan kedua, kriteria pelanggaran kepentingan umum sebagai dasar atau alasan pengajuan permohonan Pembubaran Perseroan Terbatas oleh Kejaksaan . Metode penelitian yang digunakan adalah penelitian hukum yuridis normatif dengan menggunakan pendekatan perundang-undangan dan konseptual . Hasil penelitian menunjukkan pertama, k ewenangan Kejaksaan mengajukan permohonan pembubaran Perseroan Terbatas diatur dalam pembukaan alinea ke IV UUD NRI 1945 yang berisi tujuan Negara ialah menciptakan kesejahteraan umum, ketertiban umum. Apabila terdapat Perseroan Terbatas yang dapat menghambat tujuan Negara, maka Negara memberikan kewenangan kepada Kejaksaan. Kejaksaan sebagai Pengacara Negara untuk memohonkan Pembubaran tersebut; dan kedua, kriteria Pelanggaran Kepentingan Umum yang dilakukan Perseroan Terbatas menurut Kejaksaan antara lain mencakup mengganggu kepentingan negara, masyarakat luas, kepentingan bangsa. Maka Kejaksaan harus teliti dan mengetahui apa saja kriteria Pelanggaran Kepentingan Umum berdasarkan dari berbagai Undang-Undang yang mengatur mengenai apa itu kepentingan umum.